Aztreonam inhalation solution for suppressive treatment of chronic Pseudomonas aeruginosa lung infection in cystic fibrosis - Assael, Baroukh Maurice (Expert review of anti-infective therapy, 2011)
An aerosol form of aztreonam lysinate has recently been developed as a treatment for cystic fibrosis patients suffering from chronic Pseudomonas aeruginosa lung colonization. Local administration means the drug can reach mucus concentrations in the order of hundreds of times the MIC 50 of Pseudomonas associated with severe lung disease in cystic fibrosis, resulting in a significant reduction in airway bacterial density and a parallel improvement in lung function. These advantages are maintained over prolonged periods of treatments. Administration of the drug is optimized by the use of a specific eFlow ® system, resulting in considerable reductions in treatment times when compared with conventional nebulizers. The drug has been proven safe and no concomitant induction of resistance to Pseudomonas was found during the clinical trial period of 18 months. Aztreonam lysinate has been shown to ameliorate pulmonary function in cystic fibrosis patients with chronic airway Pseudomonas infection and this is paralleled by a reduction in bacterial density in the lungs. The increased availability of new aerosolized antibiotics for cystic fibrosis will lead to new scenarios in the treatment of the disease.